Molluscan Faunas of the Lower Flagstaff Formation, Fairview Canyon, Sanpete County, Utah - Mark B. Baldy (Hello World!, 1968)
The purpose of this project was to investigate quantitative and qualitative changes in the molluscan faunas of the lower Flagstaff Formation in the Fairview Canyon, Sanpete County, Utah. The data were obtained by collecting information from each unit of a measured stratigraphic section. The field work was done during the summer of 1967 and the labratory work in the Autumn Quarter of the same year.